The effects of regular exercise on cognitive and cardiometabolic health in testicular cancer survivors subjected to platinum-based chemotherapy - Amiri, Ali; Slobodová, Lucia; Klepochová, Radka; Schön, Martin; Marček Malenovská, Karin; Rerková, Katarína; Pechancová, Radka; Prievalský, Martin; Litváková, Viera; Oliva, Viktor; Pluháček, Tomáš; Sedliak, Milan; et al. (Andrology, 2025)
BACKGROUND: Platinum-based chemotherapy provides curative treatment to more than 95% of patients with testicular germ cell tumor but it has negative cardiometabolic and neurological effects. Regular exercise can alleviate late chemotherapy-related toxicities. We examined the impact of a 6-month supervised aerobic-strength training on cognitive and cardiometabolic health and residual level of platinum in cancer survivors. METHODS: Twenty-eight middle-aged (42.1 ± 7.6 years) testicular germ cell tumor survivors subjected to platinum-based chemotherapy (1-8 cycles, 0-24 years ago) were recruited into exercise (n = 20) and control (n = 8) groups. Effects of 6-month exercise training on the whole-body and muscle metabolism, cognitive functions, cardiopulmonary fitness, residual plasma platinum, and plasma adiponectin were examined. RESULTS: Exercise intervention improved cardiopulmonary fitness and cognitive functions, reduced residual plasma platinum, visceral adiposity and muscle lipids, improved glucose (glycosylated hemoglobin) and lipid (high-density lipoprotein cholesterol) metabolism, and enhanced dynamics of muscle post-exercise phosphocreatine recovery. Exercise-related decline in plasma platinum was paralleled by decline of muscle glycerophosphocholines and by the enhanced metabolic flexibility during low-intensity exercise, and predicted training-induced increase in cognitive functions. CONCLUSIONS: The 6-month exercise intervention resulted in improved cognitive and cardiometabolic health in testicular germ cell tumor survivors, which was paralleled by reduced plasma platinum, providing evidence that structured supervised exercise brings multiple health benefits to testicular germ cell tumor survivors.
Keywords: dospělí; protinádorové látky; cvičení; přežívající onkologičtí pacienti; lidé; cardiometabolic health; odporový trénink; Cognition; cisplatin‐based chemotherapy; cognitive functions; memory; Resistance Training; lidé středního věku; metabolic flexibility; Cancer Survivors; Exercise; Humans; Cardiorespiratory Fitness; testikulární nádory; testicular germ cell tumor; mužské pohlaví; Antineoplastic Agents; Adult; kardiorespirační zdatnost; Neoplasms, Germ Cell and Embryonal; Male; kognice; Testicular Neoplasms; Middle Aged; germinální a embryonální nádory